(untitled) (Research, Society and Development, 2025)
This study aimed to analyze the mortality of elderly people admitted to the emergency room of a university hospital in Western Paraná, admitted to the intensive care unit (ICU) and undergoing invasive mechanical ventilation (IMV). This is an observational, retrospective and quantitative study, carried out based on the analysis of medical records of patients aged 60 or over, hospitalized between January and December 2023. Demographic, clinical and hospital outcome data were collected. Statistical analysis used the chi-square test, with a significance level of 5% (p < 0.05). The final sample included 1,569 patients, with a predominance of males (55%) and a mean age of 73 years. The majority (79.9%) were admitted to the ICU, and 33.8% required IMV. The overall mortality rate was 28.4%, being significantly higher among patients who used IMV (64.6%) and among those admitted to the ICU (24.1%). The average length of stay was 10.4 days. It is concluded that the need for ICU and IMV was associated with a higher mortality rate in hospitalized elderly people. The high vulnerability of this population reinforces the importance of management strategies that reduce complications and optimize intensive care.